(untitled) (Current Problems in Rail Vehicles, 2025)
This article deals with the application of an active wheelset steering technology in modern articulated trams. Indeed, tram lines in city centers often contain curves with very small radii, leading to a significant wheel and rail wear, a noise and vibration. The study proposes the integration of an actuator, originally developed for a conventional rolling stock, into the bogie of modern articulated trams with non-pivoting bogies and points out the challenges involved in such integration.